On the question of the definition and characteristics of the legal nature of the corporate relationship (Journal of actual problems of jurisprudence, 2018)
This article addresses some of the issues of the definition of the corporate relationship. Peculiarities of corporate relations. Issues related to corporate law, corporate governance and corporate law, cause in Kazakhstan is of great interest. Corporate relations today are an integral part of modern society. Considered the special role of corporate law as the relationship between government and corporate regulation.Key words: Corporation, joint stock company, corporate law, corporate relationship.